Diffusion-weighted MRI combined with susceptibility-weighted MRI: added diagnostic value for four common lateral ventricular tumors. (August 2018) - Yu, Yuanlin; Zhang, Hua; Xiao, Zebin; She, Dejun; Xing, Zhen; Yang, Xiefeng; Cao, Dairong
Background: Diffusion-weighted imaging (DWI) and susceptibility-weighted imaging (SWI) are reliable imaging modalities for brain tumors. However, the role of DWI and SWI in the diagnosis of common lateral ventricular tumors has not been systematically evaluated. Purpose: To evaluate the diagnostic performance of DWI and SWI in common lateral ventricular tumors. Material and Methods: Fifty-two patients with histopathologically confirmed lateral ventricular tumors were included in this study (18 with central neurocytomas, nine with ependymomas, seven with high-grade gliomas, and 18 with meningiomas). The relative minimum apparent diffusion coefficient (rADCmin ) and relative average apparent diffusion coefficient (rADCave ) measured by DWI and the intratumoral susceptibility signal intensity (ITSS) of hemorrhage acquired by SWI were calculated. These quantitative parameters were evaluated using the Mann–Whitney U test, receiver operating characteristic curve, and logistic regression analyses. Results: The rADCmin and rADCave ratios of central neurocytomas were significantly lower than those of the other neoplasms. The rADCmin and rADCave ratios of ependymomas and the rADCave ratio of high-grade gliomas were significantly higher than those of meningiomas. The ITSS score of meningiomas was significantly lower than those of the other tumors, while the score of central neurocytomas was obviously lower than those of ependymomas and high-grade gliomas. The combination of the rADC ratio with the ITSS showed no significant difference, except in discriminating between meningiomas and high-grade glioma-ependymomas. Conclusion: The rADC ratios and ITSS may be useful for differentiating common lateral ventricular tumors. The diagnostic performance may be improved with the use of the rADC ratios and ITSS scores.